Low- and High-Temperature Phenotypic Diversity of Brassica carinata Genotypes for Early-Season Growth and Development - Persaud, Leelawattie; Bheemanahalli, Raju; Seepaul, Ramdeo; Reddy, K. Raja; Macoon, Bisoondat (Frontiers in Plant Science, 2022)
Temperature is a major abiotic stress factor limiting plant growth. Information on carinata [B. carinata A. Braun,] traits response to extreme temperatures, is necessary for selecting genotypes suited for specific ecoregions, which is limiting. In the present study, twelve carinata genotypes were evaluated under low (17/09 ºC), optimum (22/14 ºC), and high (27/19 ºC) day/night temperatures at the early developmental stage. Growth and developmental traits were recorded 24 d after treatment imposition. The main effects of temperature and genotype on several shoots, roots, and physiological characteristics were measured. An increase in temperature decreased the accumulation of leaves flavonoids and increased nitrogen balance index values. Low-temperature treatment significantly inhibited the shoot and root traits in carinata. On the other hand, higher biomass partitioning, or biomass allocation was recorded towards leaf (68, 63, and 63%) and stem (23, 29, and 29%) then to root (9, 8, and 7%) across (low, optimum, and high temperatures, respectively) treatments. The maximum proportion of biomass partitioned to roots under low temperature than at the high-temperature stress. In response to low temperature, biomass partitioning root increased by 19%. A poor relationship (r² = 0.09) was found between low- and high-temperature indices, indicating differences in traits responses and tolerance mechanisms. Genotype AX17006 was identified as heat-tolerant and AX17009 as cold-tolerant among the 12 genotypes tested. When genotypes were grouped according to breed types, double haploid (AX17009) and inbred (AX17006) had better responses to low and high temperatures than the commercial check, respectively. Overall, the inbred (AX17006) showed greater cold and heat tolerance at the early growth stage. The variation in thermotolerance could be a valuable source for identifying tolerant genotypes.